Back to basics management the lost craft of leadership - Culligan, Matthew J. (Blackstone, 1993)
Over the past 20 years, the M.B.A. degree has come to symbolize the path to executive status, and thereby has become seemingly a prerequisite for aspiring business people. But the curriculum offered in many M.B.A. programs doesn't distinguish between the separate roles of administrators?those who preside?and managers?those who lead?in business.
Unabridged
Keywords: Management